Research of Emission Reduction and Efficiency Improvement of Three Way Catalyst Equipped on Carburetor Motorcycles Using Air Injection on Exhaust Manifold - Nguyen, Duy Tien; Khong, Vu Quang; Pham, Huu Tuyen; Nguyen, The Luong (Old Journal, 2019)
Adding air into the engine exhaust has long been considered an effective method to utilize heat to enhance the oxidation reaction in the exhaust manifold. Moreover, the addition air will overcome the limitations of using the Three Way Catalyst (TWC) for gasoline engine equipped with carburetor fuel system since it improved the oxidation environment in the catalyst. Consequently improving the conversion efficiency of CO and HC. In this paper, we will evaluate the effect of adding air into the exhaust manifold to engine performance parameters, emissions and conversion efficiency of TWC. The results show that the performance parameters of the engine, addition air were adjusted so that the equivalence ratio (λ) maintaining at approximately 1, do not change much (brake power reduction 1.67%, fuel consumption increase 2.18%). While emissions and conversion efficiency of TWC are significantly improved (conversion efficiency of CO, HC increased sharply).